OPTIMALISASI PERAN PERPUSTAKAAN UNTUK MENINGKATKAN MINAT BACA MAHASISWA - Ida Bagus Kt Dirman; I Ketut Dirga Wiratma; I Wayan Ardita Aribayu; I Wayan Rudiarta (STAH Dharma Sentana Sulawesi Tengah, 2026)
Libraries are the heart of academic activities at every level of educational units, including in universities. The library of the Gde Pudja State Hindu Institute of Mataram is a facility used to increase reading interest, but minimal visits result in a decrease in students' interest in reading. This research uses a qualitative approach or classified as descriptive research. This research was carried out at the Library of the State Hindu Institute of Gde Pudja Mataram. Starting from participant observation, structured interviews, to data processing and preparation with a total of 5 informants. The purpose of this study is to conduct an analysis related to optimizing the role of libraries in an effort to increase students' reading interest at the Gde Pudja Mataram State Hindu Religious Institute so that students will have a high level of reading interest. This study uses a descriptive qualitative method with observational techniques and structured interviews. The results of the study indicate that factors such as the availability of varied reading materials, comfortable library environmental conditions, and interactive and interesting activities have a direct influence on students' interest in reading. Therefore, it is necessary to take strategic steps to update the collection, improve facilities, and hold activities that can attract the attention of students. This study concludes that library optimization can improve students' reading culture, thereby encouraging their academic and intellectual development. By overcoming these challenges, libraries can transform into dynamic and relevant learning centers in the digital era